Role of the EF-hand-like motif in the 14-3-3 protein-mediated activation of yeast neutral trehalase Nth1 - Kopecka, Miroslava; Kosek, Dalibor; Kukacka, Zdenek; Rezabkova, Lenka; Man, Petr; Novak, Petr; Obsil, Tomas; Obsilova, Veronika (The Journal of biological chemistry, 2014)
Trehalases hydrolyze the non-reducing disaccharide trehalose amassed by cells as a universal protectant and storage carbohydrate. Recently, it has been shown that the activity of neutral trehalase Nth1 from Saccharomyces cerevisiae is mediated by the 14-3-3 protein binding that modulates the structure of both the catalytic domain and the region containing the EF-hand-like motif, whose role in the activation of Nth1 is unclear. In this work, the structure of the Nth1·14-3-3 complex and the importance of the EF-hand-like motif were investigated using site-directed mutagenesis, hydrogen/deuterium exchange coupled to mass spectrometry, chemical cross-linking, and small angle x-ray scattering. The low resolution structural views of Nth1 alone and the Nth1·14-3-3 complex show that the 14-3-3 protein binding induces a significant structural rearrangement of the whole Nth1 molecule. The EF-hand-like motif-containing region forms a separate domain that interacts with both the 14-3-3 protein and the catalytic trehalase domain. The structural integrity of the EF-hand like motif is essential for the 14-3-3 protein-mediated activation of Nth1, and calcium binding, although not required for the activation, facilitates this process by affecting its structure. Our data suggest that the EF-hand like motif-containing domain functions as the intermediary through which the 14-3-3 protein modulates the function of the catalytic domain of Nth1.
Keywords: Bmh; Protein Structure; Calcium; Trehalase; molekulární modely; Enzyme Mechanisms; 14-3-3 Proteins; katalytická doména; SAXS; trehalasa; Mass Spectrometry (MS); 14–3-3; H/D Exchange; proteiny 14-3-3; vápník; aktivace enzymů; Enzyme Activation; Saccharomyces cerevisiae - proteiny; sekvence aminokyselin; Saccharomyces cerevisiae; EF Hand Motifs; motivy EF-ruky; Protein Cross-linking; Neutral Trehalase; Catalytic Domain; Models, Molecular; Saccharomyces cerevisiae Proteins; Amino Acid Sequence